Carbapenemase Genes blaOXA23 and blaOXA58 Distribution among Acinetobacter baumanii Isolated from Clinical Isolates - Raheem, Eman J.; Al-Azawi, Ibtisam Habeeb (Medical Science Journal for Advance Research, 2025)
Background: Acinetobacter baumannii is one of the most prevalent Gram-negative microbes associated with serious and fatal nosocomial infections. It is routine to use carbapenems as a treatment for A. baumannii infections. The dissemination of carbapenem resistance offers a major challenge to the treatment of life-threatening infections caused by these bacteria. Aim of Study: Determine which isolate of carbapenem-resistance A. baumannii have higher prevalence of the blaOXA23 and blaOXA58 gene at Al-Najaf city. Settings and Design: Cross-Sectional study. Methods and Materials: From December 2023 to July 2024, a total of 220 samples were collected in this cross-sectional study including urine (n=85,39%), wounds (n=55,25%) burns (n=45,20 %), sputum (n=20, 9%), blood (n=15, 7%) from patients at Al-Sadder Medical City, burn center unit, and private laboratories in Al-Najaf city. The identification and antibiotic susceptibility profile of A. baumannii were done by vitek2 compact system. The isolates were treated for PCR assays with specific primers for (blaOXA-23 gene, blaOXA-58 gene).Results: The recovery rate of A. baumannii isolates was (n= 16, 7.27%) from different clinical samples. Antibiotic-susceptibility patterns demonstrated that isolate of A. baumannii these isolates were multi-drug resistant (MDR). The MDR isolates were resistant to all 11 antibiotics classes tested in this study. The prevalence of blaOXA-23 gene (75%) was higher than blaOXA-58 gene (31.25%) in A.baumannii isolates Conclusion: Increased resistance to carbapenem antibiotic in Al-Najaf Hospitals serves to highlight how critical this issue is when treating multidrug-resistant A. baumannii infections that are life-threatening.